World mission : an analysis of the world Christian movement - Lewis, Jonathan, 1949-; Crossman, Meg; Hoke, Stephen (William Carey Library, 1994)
Back by popular demand, this work was originally three volumes in length but is now reprinted as a single volume. This manual integrates essential and relevant articles from Perspectives on the World Christian Movement Reader, and the Perspectives Study Guide, leading the student into deeper, broader mission understanding and vision by covering the Biblical/historical foundations, the strategic dimensions, and cross-cultural considerations.